Effect of particle sizes and sodium hydroxide concentrations on silica extraction from minerals obtained in Kalirejo village, Kokap, Kulonprogo, Yogyakarta - Tutik Muji Setyoningrum; Wibiana Wulan Nandari; Sri Wahyu Murni; Muhamad Maulana Azimatun Nur (Eksergi, 2021)
Silica is mainly used in the production of rubber, glass, cement, glass, ceramics, paper, cosmetics, electronics, paintings, healthcare and other industries. Kalirejo village has a potential abundant resource of silica minerals. However, to refine it, high cost of extraction should be done to obtain high purity of silica. Different refining methods influence different purity of the silica. The purpose of this research was to study the refining process of mineral rock silica from Kalirejo village, Kokap, Kulonprogo by emplying simple and cheap solid-liquid extraction. Extraction was done by varying the particle size at 100 - 200 mesh, while NaOH concentration was varied in 0.5 N to 5 N.  Results showed that minerals taken from Kalirejo village was dominated by silica (23%).  The largest extract (4.89 gram) was obtained at 200 mesh and using NaOH 5 N with yield of 15.07%. Higher NaOH and higher particle size enhanced the extraction yield. This finding could help small communities in Kalirejo village to enhance the quality of silica by employing simple and cheap extraction process.